On the coattails of globalization: migration, migrants and COVID-19 in Asia - Suhardiman, Diana; Rigg, J.; Bandur, M.; Marschke, Melissa J.; Miller, M. A.; Pheuangsavanh, N.; Sayatham, M.; Taylor, D. (Informa UK Limited, 2021)
Positioning migrants as quintessential globalisation subjects, this paper reveals how the COVID-19 pandemic has exposed the ambivalent positioning of migration as a pathway for human development. Drawing on interviews with international and domestic labour migrants from Bangladesh, India, Laos and Myanmar working in Laos, Myanmar, China, Singapore and Thailand, the paper explores the vulnerabilities, challenges and opportunities that have come with migration and how these have been reconfigured as the pandemic has progressed, disproportionately heightening migrants’ exposure to the virus and their socioeconomic precarity. Through their personal stories, the paper provides insights into the evolving livelihood pathways of migrant workers during the course of the COVID-19 pandemic, their (changing) views of migration as a route to progress, and tentatively sets out how ruptures caused by the pandemic may lead to a re-thinking of livelihood pathways for such men and women and their families.